Discussion of the relationship to nature and technology in Hinduism, Buddhism, and Jainism - Hermanni, Friedrich 1958- (2001)
The status of the human person in the cosmos is assessed differently in the various religions. In the Western religions, the human person is regarded as the “crown of creation.” In the Eastern religions, with the concept of rebirth, humans does not stand at the center of the cosmos. Nevertheless, there does seem to be a rank-ordering of living beings, since there can be either ascent or descent through karma. (Albrecht)